Changes in lumbar kinematics and trunk muscle electromyographic activity during baseball batting under psychological pressure. Issue 1 (1st January 2020) - Oshikawa, Tomoki; Morimoto, Yasuhiro; Adachi, Gen; Akuzawa, Hiroshi; Kaneoka, Koji
ABSTRACT: Psychological pressure during sports competition disturbs the ideal physical movement and causes injury. Baseball batting frequently causes trunk injuries. This study aimed to examine the influence of psychological pressure on the lumbar kinematics and trunk muscle activity during the baseball batting. Fourteen collegiate baseball players participated in this study. The participants performed bat swings under three different psychological conditions (non-pressure, pressure, and emphasized pressure). The lumbar kinematics and trunk muscle activity were measured during each bat swing. One- and two-way analyses of variance were performed to compare the lumbar kinematics and trunk muscle activity among different psychological pressure conditions. The lumbar flexion angle throughout the bat swing in the swing phase, from the moment of ground contact of the lead foot to the moment of ball contact, was significantly larger under the pressure and emphasized pressure conditions than under the non-pressure condition (P<0.05). The bilateral lumbar erector spinae (LES) activities in the swing and follow-through phases were significantly higher under the emphasized pressure condition than under the non-pressure condition (P<0.05). These results indicate that the baseball batting under psychological pressure influenced the lumbar kinematics and bilateral LES activities and may be related to the development of low back pain.